Production of reinforced composites with natural fibers for industrial applications - Extrusion and injection WPC - Leão, Alcides Lopes [UNESP]; Fernandes Teixeira, Rui Manuel; Ferrao, Paulo Cadete (Taylor & Francis Ltd, 2008)
The aim of this work is to study the replacement of currently used thermoplastics by composites reinforced with vegetable fibers with several advantages, mainly better mechanical properties, low weight and competitive cost compared to its counterparts. Extrusion and injection molding processes were studied using polypropylene (PP) matrix. The raw materials used were sugar cane bagasse, elephant grass, wood, milk cartons and recycled polypropylene. The composites were tested for bending, tension, hardness and impact resistance, following ASTM standards. The results obtained were extremely positive since they proved that natural fibers as reinforcement can be an important alternative to replace talc and other fillers.
Keywords: bagasse; composites; elephant grass; natural fibers